Radiative Feedback Effects during Cosmic Reionization. Issue Volume 11:Issue S308(2015) (12th October 2016) - Sullivan, David; Iliev, Ilian T.
Abstract: We present coupled radiation hydrodynamical simulations of the epoch of reionization, aimed at probing self-feedback on galactic scales. Unlike previous works, which assume a (quasi) homogeneous UV background, we self-consistently evolve both the radiation field and the gas to model the impact of previously unresolved processes such as spectral hardening and self-shielding. We find that the characteristic halo mass with a gas fraction half the cosmic mean, Mc ( z ), a quantity frequently used in semi-analytical models of galaxy formation, is significantly larger than previously assumed. While this results in an increased suppression of star formation in the early Universe, our results are consistent with the extrapolated stellar abundance matching models from Moster et al. 2013.